2013
DOI: 10.1016/j.jyp.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Compilation of a herbal medicine formulary for herbal substances in Malta and its usefulness amongst healthcare professionals

Abstract: a b s t r a c tContext: Today, the use of herbal medicine for primary healthcare has increased considerably. Since local pharmacists graduate with little knowledge on herbal medicine, the majority are ill-equipped to provide pharmaceutical advice. Aims: To develop and evaluate a herbal medicine formulary to aid healthcare professionals (HCPs) in the prescribing, dispensing and counselling responsibilities. Settings and Design: Community pharmacies. Methods and Material: Monographs on all herbal substances avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…In an attempt to improve evidence-based practice among pharmacists and physicians, developing and evaluating a formulary of herbal medicinal products available in local pharmacies were done in Malta. The finding was improved quality, evidence-based prescribing together with enhanced monitoring and improved patient care [ 27 ]. Therefore, similar interventions may be appropriate in Ethiopia as well.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to improve evidence-based practice among pharmacists and physicians, developing and evaluating a formulary of herbal medicinal products available in local pharmacies were done in Malta. The finding was improved quality, evidence-based prescribing together with enhanced monitoring and improved patient care [ 27 ]. Therefore, similar interventions may be appropriate in Ethiopia as well.…”
Section: Discussionmentioning
confidence: 99%
“…The completeness of the drug is very closely related to the number of herbal medicine variations in the pharmacy. The results showed that more variations in herbal medicines would increase the use of public 10 . In regulating variations of herbal medicines requires the presence of pharmacists in the procurement of herbal medicines, and can influence patients in using drugs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The information about herbal drugs which could be found on Internet is often incomplete and inaccurate (26). The knowledge that pharmacists have about herbal remedies can also be described as highly controversial (27)(28). Only 35% of pharmacists who participated in the study was conducted in Estonia (29) reported that they did not have problems with delivery of herbal drugs, while 38.5% of them recognized the importance of continuing education for the appropriate delivery of herbal drugs.…”
Section: Table 2 Crude and Adjusted Odds Ratio For Characteristics Amentioning
confidence: 99%